2017
DOI: 10.1371/journal.pone.0190008
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum aluminum levels and cardiothoracic ratio in patients on chronic hemodialysis

Abstract: The cardiothoracic ratio (CTR) and serum aluminum levels are both associated with mortality in hemodialysis patients. However, limited data regarding the association between serum aluminum levels and the CTR have been published to date. Therefore, we aimed to elucidate this association in patients on chronic hemodialysis (CHD). We investigated the association between the serum aluminum level and the CTR in CHD in a retrospective cross-sectional study of 547 Taiwanese patients on CHD. The mean age of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The average blood aluminum level of the dialysis patients was 1.0 ± 0.4 µg/dL, below the cutoff value set by National Kidney Foundation. As shown in Table 3 [ 14 , 17 , 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], there is a decreasing trend of blood aluminum levels in the dialysis units throughout the world. In the earlier studies, Neiva et al [ 36 ] presented that the mean blood aluminum levels of Brazil hemodialysis patients was 4.5 ± 2.9 µg/dL, and Kazi et al [ 33 ] presented that blood aluminum levels of 22.0 ± 2.5 µg/dL in Pakistan hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average blood aluminum level of the dialysis patients was 1.0 ± 0.4 µg/dL, below the cutoff value set by National Kidney Foundation. As shown in Table 3 [ 14 , 17 , 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], there is a decreasing trend of blood aluminum levels in the dialysis units throughout the world. In the earlier studies, Neiva et al [ 36 ] presented that the mean blood aluminum levels of Brazil hemodialysis patients was 4.5 ± 2.9 µg/dL, and Kazi et al [ 33 ] presented that blood aluminum levels of 22.0 ± 2.5 µg/dL in Pakistan hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the end, the cardiac stroma exhibited a compensatory enlargement, triggering constant pathological cardiac remodeling. In a study of 547 hemodialysis patients, Wang et al [ 24 ] also identified a significant association between blood aluminum levels and cardiomegaly (cardiothoracic ratio more than 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…The CTR, which is the ratio of cardiac and thoracic diameters, is estimated according to chest X-ray [26], and is usually regarded as a predictor of left ventricular systolic dysfunction in LTHD patients [27]. We previously reported that CTR was not only related to peripheral arterial disease [28], but also had a negative impact on long-term survival in our LTHD patients [3,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is recognized as a strong predictor of mortality in the CKD population 26 . The final consideration is the hazardous effect of aluminum in cardiac remodeling 7 , 27 , which the cardiotoxicity of aluminum might be attributable to oxidative stress and dysregulation of the intracellular redox system 18 . Some reports have found a significant association between heart damage and aluminum levels 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, hyperparathyroidism might be a mechanism to protect against aluminum-induced osteomalacia, perhaps by increasing bone turnover with elevated alkaline phosphatase levels 31 . Moreover, studies found evidence for aluminum-induced cardiac injury 28 and cardiac complications 29 ; higher aluminum loading in CHD patients was associated with cardiomegaly 7 and cardiothoracic ratio (>0.5) 27 ; cardiotoxicity of aluminum might be attributable to oxidative stress and dysregulation of the intracellular redox system 18 . Such clinical findings in previous studies can support our data.…”
Section: Discussionmentioning
confidence: 99%